Testing the CVAR in the fractional CVAR model - Søren Johansen; Morten Ørregaard Nielsen (Queen's University, Department of Economics, 2017)
We consider the fractional cointegrated vector autoregressive (CVAR) model of Johansen and Nielsen (2012a) and show that the likelihood ratio test statistic for the usual CVAR model is asymptotically chi-squared distributed. Because the usual CVAR model lies on the boundary of the parameter space for the fractional CVAR in Johansen and Nielsen (2012a), the analysis requires the study of the fractional CVAR model on a slightly larger parameter space so that the CVAR model lies in the interior. This in turn implies some further analysis of the asymptotic properties of the fractional CVAR model.
Keywords: C32; 330; cointegration; fractional integration; likelihood inference; vector autoregressive model